A two-step method for additional mass identification in beam structures by measurements of natural frequencies and guided waves. (December 2021) - Sha, Ganggang; Soman, Rohan; Radzieński, Maciej; Cao, Maosen; Ostachowicz, Wiesław; Zuo, Hongfu
Highlights: A novel global–local methodology for additional mass detection in beam structures is formulated. The possible locations of the additional mass are identified using natural frequencies at the global level. The precise location of the additional mass is determined from guided wavefield imaging at the local level. The methodology is proved to be feasible through both numerical and experimental tests. Abstract: This paper presents a two-step method for the identification of additional masses in beam structures. In the first step, relative natural frequency change (RNFC) curves are developed as an indicator for identifying the possible locations of additional masses at the global level. The RNFC curves based method allows detection of possible mass locations using natural frequencies alone and as such is a significant improvement over the state of the art. To further identify the precise locations of the masses, guided wavefield imaging is used for local mass detection in the second step. The two-step method is successfully applied for the precise localization of additional masses on a simply-supported beam. The paper firstly shows that additional mass-induced RNFC curves are different from those caused by cracks in beams. As a result, a theoretical formulation and validation of additional mass identification is needed and is the main novelty of the paper.